1987
DOI: 10.1002/bip.360260704
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of the 2′‐deoxyribofuranose ring from proton–proton coupling constants: Analysis of a nucleoside‐carcinogen adduct formed from 2‐acetylaminofluorene utilizing a three‐state model

Abstract: SynopsisThe conformation of the sugar moiety of 8-( N-fluoren-2-ylamino)-2'-deoxyguanosine in solution has been examined as a function of temperature by 'H-nmr spectroscopy. Analysis of coupling constants shows that lowering the temperature to -50°C in methanol shifts the conformational equilibrium of the sugar ring resulting in a C2'-endo conformation at a mole fraction of 0.97. The computed phase angle of pseudorotation and amplitude of pucker are 154" and 36", respectively, with very little discrepancy betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The sugar ring pucker of 2'-deoxynucleosides and 2'deoxynucleotides in solution can in certain cases by determined with good resolution from the five relevant proton-proton / values (Haasnoot et al, 1981;Evans & Levine, 1987). The sugar ring is frequently described in terms of the pseudorotational parameters P and , where P is the phase angle of pseudorotation and the amplitude of pucker.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sugar ring pucker of 2'-deoxynucleosides and 2'deoxynucleotides in solution can in certain cases by determined with good resolution from the five relevant proton-proton / values (Haasnoot et al, 1981;Evans & Levine, 1987). The sugar ring is frequently described in terms of the pseudorotational parameters P and , where P is the phase angle of pseudorotation and the amplitude of pucker.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of an 04'-endo conformation in certain modified nucleosides analyzed by X-ray crystallography has been the basis for the suggestion of a three-state model (Birnbaum et al, 1979;Olson, 1981;Evans & Levine, 1987). Thus, it would be of interest to test for this possibility in the NMR spectra of d-Cp(AAFG) in aqueous solution at 20 °C show the effect of concentration on the downfield spectral region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The task of understanding how structurally similar arylamine-DNA adducts can lead to different mutagenicities and repair rates will require three-dimensional structural details of the modification sites. Although NMR methods have been used extensively for this purpose (Evans et al, 1980(Evans et al, , 1984Evans & Miller, 1982;Evans & Levine, 1987Sharma & Box, 1985;Shapiro et al, 1986), the number of reported solution NMR studies of intact arylamine-DNA adducts at the duplex level is small (Norman et al, 1989;Cho et al, 1992;O'Handley et al, 1993). This is due in part to the spectral complexities encountered in the proton NMR spectra of modified duplex oligomers (Harris et al, 1988) and to the technical difficulties in preparing carcinogen-modified oligonucleotides (Basu & Essigmann, 1988).…”
mentioning
confidence: 99%
“…High-resolution proton NMR methods have been applied to elucidate structural features of AAF-G adducts at the mononucleotide (Evans & Levine, 1987), dinucleotide (Evans & Levine, 1988), and hexanucleotide (Sharma & Box, 1985) single-strand level and at the nonanucleotide duplex level (Krugh et al, 1986). The latter NMR study addresses questions related to the conformation of (AAF)G opposite cytidine in the center of a 9-mer duplex (Krugh et al, 1986).…”
mentioning
confidence: 99%